Vicious LQT induced by a combination of factors different from hERG inhibition - Xu, Xinping; Yin, Yue; Li, Dayan; Yao, Binwei; Zhao, Li; Wang, Haoyu; Wang, Hui; Dong, Ji; Zhang, Jing; Peng, Ruiyun (Frontiers in Pharmacology, 2022)
Clinically, drug-induced torsades de pointes (TdP) are rare events, whereas the reduction of the human ether-à-go-go-related gene (hERG) current is common. In this study, we aimed to explore the specific factors that contribute to the deterioration of hERG inhibition into malignant ventricular arrhythmias. Cisapride, a drug removed from the market because it caused long QT (LQT) syndrome and torsade de pointes (TdP), was used to induce hERG inhibition. The effects of cisapride on the hERG current were evaluated using a whole-cell patch clamp. Based on the dose-response curve of cisapride, models of its effects at different doses (10, 100, and 1,000 nM) on guinea pig heart in vitro were established. The effects of cisapride on electrocardiogram (ECG) signals and QT interval changes in the guinea pigs were then comprehensively evaluated by multi-channel electrical mapping and high-resolution fluorescence mapping, and changes in the action potential were simultaneously detected. Cisapride dose-dependently inhibited the hERG current with a half inhibitory concentration (IC50) of 32.63 ± 3.71 nM. The complete hERG suppression by a high dose of cisapride (1,000 nM) prolonged the action potential duration (APD), but not early after depolarizations (EADs) and TdP occurred. With 1 μM cisapride and lower Mg2+/K+, the APD exhibited triangulation, dispersion, and instability. VT was induced in two of 12 guinea pig hearts. Furthermore, the combined administration of isoproterenol was not therapeutic and increased susceptibility to ventricular fibrillation (VF) development. hERG inhibition alone led to QT and ERP prolongation and exerted an anti-arrhythmic effect. However, after the combination with low concentrations of magnesium and potassium, the prolonged action potential became unstable, triangular, and dispersed, and VT was easy to induce. The combination of catecholamines shortened the APD, but triangulation and dispersion still existed. At this time, VF was easily induced and sustained.